Essays on business environment reforms - Passos, Danilo José Rodrigues (2023)
This thesis consists of two essays that bring new empirical evidence to the literature related to business environment reforms. The first chapter presents new evidence on the effects of easier entry regulation on the formalization of firms, by evaluating the effects of ‘Empreenda Fácil’, a program implemented in São Paulo with the objective of lowering the bureaucracy associated with opening a business in the city. Launched in 2017, the ‘Empreenda Fácil’ program unified a number of registration procedures and the delivery of documents in a single online system, and was able to entail an aggressive reduction in the number of days to start a business, from 104.5 to 18 in only one year. Results point that the program led to an increase between 12.4% and 17.6% in the registration of formal entrepreneurs in industries that were eligible to the policy. The second chapter investigates what kind of political institutions lead to better business environments or, more specifically, if democratization events have a positive impact on business environment conditions. Using panel data from 188 countries, for the period between 2011 and 2020, results reveal a positive and significant effect of democratizations on business environment quality. Those results are robust to a number of alternative indicators of democracy and business environment quality. Therefore, the results and conclusions of both chapters reinforce that business environment reforms should continue to be a relevant topic in the discussion and development of public policies.